Sisyphe à Mexico : risques et politiques urbaines - François Mancebo (VertigO)
Mexico City —locating at a height of more than 2,000 meters on the foothills of Sierra Madre and Cordillera Neovolcanica— lies in an inviting though dreadful area. It appears to be one among the most dangerous areas in the world as far as risk is concerned: exposed to all type of natural risks, to technological hazards linked to heavy industry, to air and water pollution and to exhaustion of all exploitable local resources. After 1985's earthquake, planners and developers of Mexico City have been integrating risk mitigation and sustainability in urban policy. But this new direction turned hardly applicable. The reason is an all-prescriptive and centralized tradition combining with complete lack of interest in peripheral districts, which resources are solely exploited to improve sustainability of wealthy, touristic or historic metropolitan areas (actually creating an imported sustainability artifact). In much the same way as in Sisyphus myth, mexican planners and developers try hard to take the risk-boulder up the unsustainable-slope, but the boulder always comes down, again and again. In reality, the boulder is not the problem. The problem lies in not considering the slope's profile on which the boulder rolls, i.e. its substratum made of risk perceptions, territorial representations and local practices.